2015
DOI: 10.1021/acs.inorgchem.5b01446
|View full text |Cite
|
Sign up to set email alerts
|

A trans-1,2 End-On Disulfide-Bridged Iron–Tetracarbene Dimer and Its Electronic Structure

Abstract: A disulfide-bridged diiron complex with [Fe-S-S-Fe] core, which represents an isomer of the common biological [2Fe-2S] ferredoxin-type clusters, was synthesized using strongly σ-donating macrocyclic tetracarbene capping ligands. Though the complex is quite labile in solution, single crystals were obtained, and the structure was elucidated by X-ray diffraction. The electron-rich iron-sulfur core is found to show rather unusual magnetic and electronic properties. Experimental data and density functional theory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
1
26
1
Order By: Relevance
“…We assume this scrambling reaction to occur via attack of the Fe IV =O unit at a Fe atom of the Fe III ‐O‐Fe III core, trans to the μ‐oxo ligand (Scheme ). DFT calculations had shown that the square‐pyramidal coordinated ferric ions in 1 adopt an intermediate spin state ( S =3/2) with electron configuration (Fe d xy ) 2 π*(Fe d xz , yz ) 2 σ*(Fe dz2 ) 1 σ*(Fe dx2-y2 ) 0 . Thus, the antibonding dz2 orbital is singly occupied and five‐fold coordination without a MeCN ligand in the axial position trans to the μ‐O is favored over six‐fold coordination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume this scrambling reaction to occur via attack of the Fe IV =O unit at a Fe atom of the Fe III ‐O‐Fe III core, trans to the μ‐oxo ligand (Scheme ). DFT calculations had shown that the square‐pyramidal coordinated ferric ions in 1 adopt an intermediate spin state ( S =3/2) with electron configuration (Fe d xy ) 2 π*(Fe d xz , yz ) 2 σ*(Fe dz2 ) 1 σ*(Fe dx2-y2 ) 0 . Thus, the antibonding dz2 orbital is singly occupied and five‐fold coordination without a MeCN ligand in the axial position trans to the μ‐O is favored over six‐fold coordination.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the antibonding dz2 orbital is singly occupied and five‐fold coordination without a MeCN ligand in the axial position trans to the μ‐O is favored over six‐fold coordination. For comparison, the metal ions in trans ‐1,2 end‐on disulfido‐bridged [(MeCN)(L NHC )Fe III SSFe III (L NHC )(MeCN)] 4+ are coordinated octahedrally with additional MeCN ligands, in agreement with their S =1/2 spin states (electron configuration (Fe d xy ) 2 π*(Fe d xz , yz ) 3 σ*(Fe dz2 ) 0 σ*(Fe dx2-y2 ) 0 ), but this disulfido‐bridged iron(III) dimer readily decomposes in solution with loss of S x . Consequently, we propose that axial coordination ( trans to the μ‐O) at 1 (or 1 Me16 ) by either MeCN, PrCN, or by the Fe IV =O unit of 2 induces cleavage of the Fe‐O‐Fe bridge.…”
Section: Methodsmentioning
confidence: 99%
“…Iron(II) compounds coordinated by a macrocyclic tetracarbene were used by Meyer et al to generate the first organometallic oxoiron(IV) complex. According to magnetic measurements, the oxoiron(IV) complex reveals an intermediate‐spin state S = 1, which was rationalized by strong stabilization, using the excellent σ‐donor NHC, which leads to an energetically rather high‐lying d x ²– y ² orbital …”
Section: Introductionmentioning
confidence: 99%
“…For example, the tetracarbene coordinated iron complexes reported by Meyer et al typically show very large QS parameters. [153,156] The strong equatorial σ-donor system leads to an oblate and therefore non-cubic charge distribution around the nucleus. More examples in this context will be given within this thesis.…”
Section: Hyperfine Interactions In Mössbauer Spectroscopymentioning
confidence: 99%
“…species 3 and a trans-1,2 end-on disulfide-bridged iron dimer 3 SS (Scheme 9). [153,156] Iris Klawitter studied the reactivity of 1 versus azide compounds and sythesized complexes 5 and 6. [155] The µ-nitrido compound 6 has been the first example of an Fe III -N-Fe III system and highlights the ability of the carbene ligand in making model systems with iron in unusual oxidation states available.…”
Section: Introduction Into a Macrocyclic Tetracarbene Ligand Systemmentioning
confidence: 99%